Comments on “Devonian to Permian post-orogenic denudation of the Brasília Belt of West Gondwana: Insights from apatite fission track thermochronology” by Fonseca et al. (2020) - Alessandretti, Luciano; Warren, Lucas Veríssimo [UNESP] (Elsevier, 2022)
In a recent paper published in the Journal of Geodynamics (vol. 137, June 2020, 101733), Fonseca et al. (2020) proposed a thought-provoking model aiming to elucidate the exhumation history of the Neoproterozoic Brasília Fold Belt (BFB) between the Devonian and Cretaceous periods. Exclusively based on information from the literature and new thermochronological data, Fonseca et al. (2020) presented an alternative model that tries to bind tectonic uplift, erosion, and the influx of clastic material coming from the BFB into the intracratonic Paraná Basin. Although the welcome proposal and reliable quality of the analytical data, the hypothesis presented diverges from several previously published works. In the light of the presented apatite fission-track ages, we disagree with their paleogeographical model, which puts the Brasília Fold Belt as a major source for clastic detritus to the Paraná Basin between the Devonian to Permian. The primary goal of our comments is to clarify the state-of-art of the intricate source-to-sink system of the Paraná Basin. Secondarily, we try to demonstrate why the model proposed by Fonseca et al. (2020) presents some geodynamic and interpretative problems and do not characterize an adequate paleogeographic scenario for southwest Gondwana between the Devonian to Permian periods.
Keywords: Brasília Fold Belt; Devonian; Paraná Basin; Permian; Source-to-sink; West Gondwana